The End of the Tunnel: Girls' Marked Bodies in the Canadian Transcarceral Pipeline. Issue 3 (1st December 2021) - de Finney, Sandrina; Mucina, Mandeep Kaur
Abstract: In settler states, Black, Indigenous, and people of color (BIPOC) girls and young women are targeted for specific kinds of social service interventions embedded in the gendered genocidal logics of colonial ideologies. Interlocking forms of violent carceral capture operate across settler institutions such as child welfare, immigration, and justice systems that are tasked with policing and criminalizing nonwhite girls. Conceptualizing these interconnected systems as a transcarceral pipeline, we examine their inner workings and impacts on Indigenous girls and BIPOC refugee girls in Canada through two sites of inquiry: child welfare systems targeting Indigenous girls and young mothers; and the immigration-child-welfare pipeline for refugee girls of color. Our analysis stresses the urgency of anticolonial systems of care grounded in sovereignty-making collective relations.